063 Age-appropriateness of common neuromuscular training exercises in ACL injury prevention programs. (3rd March 2020) - Ling, Daphne; Boyle, Caroline; Janosky, Joseph; Chang, Brenda; Roselaar, Naomi; Kinderknecht, James; Marx, Robert
Abstract : Background: The appropriateness of neuromuscular training exercises across different age groups has not yet been investigated, particularly in younger children. Objective: This study will determine which neuromuscular training exercises can be performed with proper alignment in various age groups. Design: Cross-sectional study. Setting: Youth athletes in a controlled setting. Participants: Children ranging from 8–17 years of age were recruited from schools and youth sports organizations. A total of 360 participants were evaluated (8–11 years: 165, 54% female; 12–15 years: 136, 40% female, 16–17 years: 59, 53% female). Interventions: Seven exercises were selected for evaluation. Participants completed two trials of each exercise and were judged on maintaining neutral body alignment after receiving visual/verbal instruction on the first trial and feedback cues on the second trial. Main outcome measurements: Three evaluators judged each exercise, which was deemed as correct when at least two evaluators agreed that neutral alignment was maintained. Comparisons were made across ages and between sex using the Chi-squared test or Fisher's exact test. The proportions of participants who performed the exercise correctly were also compared before and after feedback cues were provided. Results: There were no significant differences in performance across ages and sex for nearly all exercises. Most neuromuscular training exercises had a less than 50% success rate for proper neutral alignment in children 8–17 years of age. The use of visual and verbal feedback cues significantly increased the proportion of participants who correctly completed the exercise (p<0.001). Inter-rater reliability among the evaluators ranged from kappa=0.31 to 0.42, showing fair to moderate agreement. Conclusions: These results demonstrate the importance of training coaches and physical education teachers to provide cues that reinforce proper technique during ACL injury prevention exercises. Children should perform common neuromuscular training exercises with feedback on proper technique. The availability of age-appropriate exercises may help increase adherence to injury prevention programs and maximize their effect on reducing injuries.